PROBLEMS OF MASTERING THE BASIC DISCIPLINES BY STUDENTS OF TECHNICAL FIELDS OF TRAINING IN THE CONDITIONS OF THE MILITARY STATE OF UKRAINE - STRUTYNSKA, LESIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Based on the analysis of the level of residual knowledge of students of junior bachelor's level training in mechanical specialties from the disciplines of natural sciences, the effect of distance learning of graduates of secondary education on the success of first-year students in basic disciplines was investigated. Higher mathematics, physics, chemistry and descriptive geometry as a section of mathematics are included in the cohort of basic disciplines of the fundamental training of specialists in mechanical specialties. The research was carried out on the basis of analyzes of slices of knowledge from basic disciplines in the form of test tasks of first-year students at the initial stage of their studies at a higher education institution. The results of these data are compared with the results of students passing the exam and credit session in these academic disciplines. The study was conducted on the basis of analyzes of the success of full-time students of the Institute of Mechanical Engineering and Transport (IMIT) of the Lviv Polytechnic National University (LU). For the years of comparative analysis of success, the years 2019-2020 were chosen, which preceded the introduction of distance learning due to the coronavirus pandemic, and 2023-2024 with a combined scheme for conducting the educational process, which alternates face-to-face classroom and distance learning depending on the security situation caused by the conduct of intensive combat actions on the territory of Ukraine.The results of the comparative analysis established that the remote form of conducting the educational process both in secondary education institutions and in the educational process of a higher school ensures the continuity of the educational process. However, the level of success and the amount of residual knowledge of both secondary and higher education students is rapidly decreasing.It is proposed to eliminate the shortcomings of distance learning in institutions of the higher council for students of technical fields of training to revise the curricula and training programs with the aim of increasing hours and credits for the basic disciplines, aimed at eliminating the shortcomings of distance learning at the previous stages of their education.Taking into account the peculiarities of the educational process in the conditions of martial law, it is proposed to supplement traditional educational classes in basic disciplines with their dubbing in the form of video films and educational videos, which will be held on working days of the week in the evening, and on weekends - at times agreed with the students. Attendance by students of these additional educational and counseling classes should be recorded, but voluntary.
Keywords: mechanical engineering; engineering; specialty; education; distance learning; quality of education; technical areas of training